2012
DOI: 10.1186/bcr3095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of patient-derived breast cancer xenografts

Abstract: IntroductionIdentification of new therapeutic agents for breast cancer (BC) requires preclinical models that reproduce the molecular characteristics of their respective clinical tumors. In this work, we analyzed the genomic and gene expression profiles of human BC xenografts and the corresponding patient tumors.MethodsEighteen BC xenografts were obtained by grafting tumor fragments from patients into Swiss nude mice. Molecular characterization of patient tumors and xenografts was performed by DNA copy number a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 26 publications
10
160
1
2
Order By: Relevance
“…Though few studies have focused on the genomic similarities of patient tissue and primary xenografts, those published suggest that mutations are generally conserved. 15,16 In addition, because these models are established under more physiological conditions (ie, temperature, oxygen levels, nutrient content etc. ), they may be appropriate for representing human cancers in specific settings.…”
mentioning
confidence: 99%
“…Though few studies have focused on the genomic similarities of patient tissue and primary xenografts, those published suggest that mutations are generally conserved. 15,16 In addition, because these models are established under more physiological conditions (ie, temperature, oxygen levels, nutrient content etc. ), they may be appropriate for representing human cancers in specific settings.…”
mentioning
confidence: 99%
“…L'analyse en classification non supervisée a montré la remarquable stabilité génomique des xénogreffes de cancers colorectaux pendant les dix premiers passages au moins. Cette caractéristique a d'ailleurs déjà été observée pour d'autres séries de xéno-greffes [6,7]. Cependant, l'apparition de quelques altérations de novo, absentes dans les tumeurs d'origine, pourrait s'expliquer par l'expansion clonale d'une population minoritaire et/ou par la poursuite dans la xénogreffe du processus de mutation qui avait commencé dans la tumeur issue du patient.…”
Section: Caractérisation Moléculaire Des Tumeurs D'origine Et Des Tumunclassified
“…In contrast to in vitro propagated cultures, cytogenetic analyses of PDX models reveals strong preservation of the chromosomal architecture observed in patient tumors. 28,62 PDX models of melanoma, breast, pancreatic, ovarian, lung, colorectal, and brain-derived tumors have been successfully established in many laboratories (reviewed by Tentler et al 29 ), and many have proven to exhibit similar chemoresponsiveness to anti-neoplastic agents as observed in the same donating patient in the clinicunderscoring the fidelity of these models to the natural disease state 30,63 (unpublished results).…”
Section: Pdxs: Models For the 21st Centurymentioning
confidence: 99%
“…First, patient-derived xenograft (PDX) tumor models are increasingly feasible and available. [26][27][28][29] Second, evidence is amassing that supports the cancer stem cell (CSC) paradigm: a theoretical model for cancer that accounts for the importance of specific tumor cell subpopulations to a tumor's growth and potential for driving tumor recurrence (reviewed in previous studies [30][31][32] ). Finally, next-generation DNA and RNA sequencing efforts (eg, The Cancer Genome Atlas) have demonstrated that very few common mutations unite particular solid tumor types; rather, patient tumors have a spectrum of mutations that collectively drive tumor growth.…”
Section: Addressing Tumor Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation